RESPIRATORY TRACT INFECTIONS IN BSH CATS - Putu Aditya Pratama Artha Putra; Putu Devi Jayanti; I Gusti Made Krisna Erawan (Buletin Veteriner Udayana, 2024)
Respiratory tract infection (ISP) is a disease that often occurs in cats kept in crowded environments. This condition is the main cause of high morbidity and mortality in cats. The purpose of writing this article is to diagnose respiratory tract infections (ISP). An 8-month-old male cat named Ruby was brought by his owner to the Veterinary Internal Medicine Laboratory, Faculty of Veterinary Medicine, Udayana University with complaints of sneezing and mucopurulent discharge from the nose for approximately two months and accompanied by coughing for the past month. On physical examination, the case cat had tachypnea, mucopurulent nasal discharge, and gingivitis. The mandibular lymph nodes are symmetrically swollen. X-ray examination results showed increased opacity in the lungs. Routine hematological examination showed that the case cat had neutrophilia. The cat was diagnosed with a respiratory tract infection (ISP) in the form of chronic rhinitis and bronchopneumonia. The treatment given was the antibiotic doxycycline hyclate as causative therapy, the anti-inflammatory methylprednisolone orally and the antihistamine chlorpheniramine maleate orally as symptomatic therapy, and fish oil as supportive therapy. The results of two weeks of therapy showed that the animal in the case had experienced changes, namely that the nasal discharge had disappeared, the frequency of sneezing and coughing had decreased and the cat's gums were no longer inflamed.